The long-feared backlashes of targeting LGBT+ consumers: What can fashion brands expect when using immersive technologies in advertising? - Pinho, A.; Loureiro, S. M. C. (2021 Global Fashion Marketing Conference, 2021)
Companies are still afraid of targeting LGBTI+ population. To extend research, authors apply sequential studies to explore the immediate and long-term effects of LGBTI+ imagery in fashion brands. Built on Stimulus-Organism-Response Model, authors present advertisements in print and immersive technology formats and measure viewers’ self- reported answers and physical changes.